Low-tech Innovation : Competitiveness of the German Manufacturing Sector - Som, Oliver; Kirner, Eva (Springer International Publishing : Imprint: Springer, 2015)
This book highlights the economic relevance of the so-called low-tech industries and firms. Non R&D intensive firms continue to be the economic backbone of several developed industrial countries. They form the core of National Innovation Systems and contribute significantly to growth and employment. However, due to their lack of R&D activity, they are easily overlooked in the general innovation debate. This book provides latest empirical findings on the current economic relevance and specific innovation strategies and management of non-R&D intensive firms in Germany. It discusses their future role in a knowledge driven economy as well as possible implications for innovation and technology policy. An outcome of several years of dedicated research conducted at the Fraunhofer Institute for Systems and Innovation Research (ISI), this book will prove of immense value to researchers and policy makers dealing with innovation and knowledge strategy.